Buenas prácticas de manejo agrícola en el establecimiento de pastos mejorados - Troya Mora, Darwin Manuel (2024)
Improved pastures are of great importance to the livestock sector, as they play a relevant role in the sustainable intensification of livestock production in Ecuador. Most of the Ecuadorian territory has favorable environmental conditions for producing pastures all year round. The use of pastures contributes to production and competitiveness. However, establishing improved pastures presents a great challenge, due to the lack of knowledge and high costs for a pasture to be established properly and be profitable. However, the livestock sector is in a limited development due to various factors that affect pastures and the lack of knowledge when managing improved pastures, which are the main source of food for the animal species used in livestock farming. Therefore, the research topic of determining good agricultural practices for the management of improved pastures was raised. The efficient management of improved pastures allows farmers to have forage throughout the year, especially in periods of drought. This process also mitigates the effects of overgrazing and soil compaction in highland grazing areas (such as grasslands and oconales). For the above reasons, this research seeks to provide the necessary information to establish grasslands that are managed with specific practices to make better use of them, which impact on their normal development and affect the development of the country's livestock sector.